Determinants of low-value imaging for patients with low-to-intermediate risk microscopic hematuria. Issue 28 (1st October 2022) - Birken, Sarah A; Peluso, Alexandra; Wagi, Cheyenne; Bundy, Richa; Witek, Lauren; Krol, Bridget C.; Pathak, Ram; Nielsen, Matthew E.; Matulewicz, Richard; Parchman, Michael L.; Dharod, Ajay
Abstract : 27 Background: In the US, two million people are referred to urologists for the evaluation of microscopic hematuria (MH). MH guidelines were revised in 2020 by the American Urological Association, recommending that only patients at high risk for malignancy based on age, smoking history, or urinalysis receive computed tomography (CT) imaging. We found in previous studies that providers continued to use CT for patients with low-to-intermediate risk, representing low-value care. To understand reasons for continued CT use for patients with low-to-intermediate risk MH, we assessed determinants of low-value care in a concurrent mixed-method study. Methods: We stratified patients with a urology consultation within 180 days of a urinalysis documented in one academic medical center's electronic health record between 1/1/15 and 7/1/21 into high-, intermediate-, and low-risk categories and validated risk designation in a chart review of a 5% subsample. We defined low-value care as CT for patients with low-to-intermediate-risk MH. To assess determinants of low-value MH care, we conducted semi-structured interviews with primary, urology, and gynecology providers (n = 7) identified through our professional networks. Results: Six hundred nineteen patients were referred to urology for MH. 58.6% were high-risk, 33.6% intermediate-risk, 4.4% low-risk, and 3.4% were undefined. 15.9% of intermediate-risk (n = 33) and 11.1% of low-risk (n = 3) patients received CT. Of the 14 patients referred to urology post-guideline change, none with low-to-intermediate-risk received CT. Interviews demonstrated substantial variation in approaches to MH evaluation. Urologists were largely aware of the revised guideline but noted inappropriate evaluation before referral, unnecessary referrals, and inefficiency in evaluation following referral. Lacking accessible data for risk stratification, other providers' approaches were varied but driven by a common goal of ruling out renal malignancy, based on medical school training and institutional norms. Conclusions: Low-value care was limited but persistent and may be driven by a lack of resources to support risk-stratified MH evaluation, including accessible risk stratification data and clear guidelines for appropriate evaluation. This is consistent with a lack of practical guidance for implementing MH evaluation guidelines. In future studies, we will develop strategies to facilitate risk-stratified MH evaluation in practice.